Research on air pollution by diesel engine / Yanty Katarina Asyikin Yusof and Ida Zawani Ismail - Yusof, Yanty Katarina Asyikin; Ismail, Ida Zawani (2003)
Clean environment can be defined as the nature which is free from any type of pollution whether pollution in the water, air, soil etc. This research will show us about the pollution made by transportation sector. It is one of the sectors that contribute most to the air pollution based on the data that we had gained mostly from Department of Environment. Even though our country, Malaysia is moving to become an industrial country, we should not neglect the importance of clean environment. By considering that, our government bodies such as Department Of Environment is trying to overcome the problems in many different ways to make sure that transportation sector especially diesel engine vehicles obey to all rule set by them in order to control air pollution. Any vehicles which disobey the rules which is set by Department Of Environment will be compounded. Beside, we will also showed the number of complaints received by Department of Environment for air pollution and enforcement taken by government bodies other than Department Of Environment such as the Road Transport Department (JPJ), Puspakom, Police Traffic Department and so on in order to control the air pollution. Lastly, all vehicles owner should cooperate with responsible government bodies in order to control the air pollution and make our environment free from any type of pollution.